2015
DOI: 10.1016/j.jnutbio.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Decaffeinated green tea extract rich in epigallocatechin-3-gallate prevents fatty liver disease by increased activities of mitochondrial respiratory chain complexes in diet-induced obesity mice

Abstract: Nonalcoholic fatty liver disease has been considered the hepatic manifestation of obesity. It is unclear whether supplementation with green tea extract rich in epigallocatechin-3-gallate (EGCG) influences the activity of mitochondrial respiratory chain complexes and insulin resistance in the liver. EGCG regulated hepatic mitochondrial respiratory chain complexes and was capable of improving lipid metabolism, attenuating insulin resistance in obese mice. Mice were divided into four groups: control diet+water (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 64 publications
(78 reference statements)
2
51
0
Order By: Relevance
“…Importantly, studies have revealed that GrTPs act dose dependently, as high doses (0.4–0.8 mg/mL) activate apoptotic pathways through caspases and DNA breakdown to provoke anti-malignant effects [17]. Also, GrTPs promote weight loss in high doses (EGCG 1.3mg/g/daily [9], 3.2 mg/g every three days [51]) which can be beneficial for the regulation of hepatic enzymes (10–20 mg/g [54]) and metabolism (500 mg tablet/day [55]), as well as in metabolic syndrome and obesity (EGCG 0.05 mg/g [52]); yet, this is a side effect in certain situations where weight loss is not favored. In addition, GrTPs and EGCG in very high doses (3.2 mg/g) require further safety trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, studies have revealed that GrTPs act dose dependently, as high doses (0.4–0.8 mg/mL) activate apoptotic pathways through caspases and DNA breakdown to provoke anti-malignant effects [17]. Also, GrTPs promote weight loss in high doses (EGCG 1.3mg/g/daily [9], 3.2 mg/g every three days [51]) which can be beneficial for the regulation of hepatic enzymes (10–20 mg/g [54]) and metabolism (500 mg tablet/day [55]), as well as in metabolic syndrome and obesity (EGCG 0.05 mg/g [52]); yet, this is a side effect in certain situations where weight loss is not favored. In addition, GrTPs and EGCG in very high doses (3.2 mg/g) require further safety trials.…”
Section: Discussionmentioning
confidence: 99%
“…EGCG (0.05 mg/g/day) oral gavage regulated hepatic mitochondrial respiratory cascades and improved lipid metabolism, and insulin sensitivity in obese mice [52]. EGCG increased energy expenditure, and prevented oxidation of lipid substrates-stimulated by mitochondria and hepatic steatosis in this obesity model.…”
Section: Hepatic Complications and Green Tea Polyphenolsmentioning
confidence: 99%
“…Important members of this subfamily include catechin, epicatechin, epigallocatechin, and the most biologically active one, epigallocatechin gallate (EGCG). Similar to other flavonoids, EGCG administered intraperitoneally or in the diet decreased body weight gain, visceral fat deposition, hyperglycemia, insulin resistance, liver functional enzymes, and hepatic steatosis following consumption of high‐fat diets (Santamarina et al, ). Decreased hepatic lipid accumulation may result from increased lipid oxidation through augmented electron transport chain activity.…”
Section: Treatment Of Non‐alcoholic Fatty Liver Diseasementioning
confidence: 98%
“…EGCG has multiple health benefits including the attenuation and prevention of liver fibrosis [16, 21, 22]. In vitro analysis shows that EGCG can abrogate liver fibrosis by inhibiting the proliferation of fibroblasts, reducing collagen deposition, and upregulating the mitochondrial respiratory chain [23]. Outside the spectrum of liver disease, EGCG can attenuate TGF-ß expression in pulmonary fibrosis [24].…”
Section: Introductionmentioning
confidence: 99%